Synthesis, in vitro and in silico studies of novel potent urease inhibitors: N-[4-(5-[(3-Un/substituted-anilino-3-oxopropyl)sulfanyl]-1, 3, 4-oxadiazol-2-ylmethyl)-1, 3-thiazol-2-yl]benzamides. Issue 13 (30th July 2018) - Abbasi, Muhammad Athar; Hassan, Mubashir; Aziz-ur-Rehman,; Siddiqui, Sabahat Zahra; Raza, Hussain; Shah, Syed Adnan Ali; Seo, Sung-Yum
Graphical abstract: Abstract: The present article describes the synthesis, in vitro urease inhibition and in silico molecular docking studies of a novel series of bi-heterocyclic bi-amides. The synthesis of title compounds was initiated by benzoylation, with benzoyl chloride (1 ), of the key starter ethyl 2-(2-amino-1, 3-thiazol-4-yl)acetate (2 ) in weak basic aqueous medium followed by hydrazide formation, 4, and cyclization with CS2 to reach the parent bi-heterocyclic nucleophile, N -4-[(5-sulfanyl-1, 3, 4-oxadiazol-2-yl)methyl]-1, 3-thiazol-2-ylbenzamide (5 ). Various electrophiles, 8a–l, were synthesized by a two-step process and these were finally coupled with5 to yield the targeted bi-heterocyclic bi-amide molecules, 9a–l . The structures of the newly synthesized products were corroborated by IR, 1 H NMR, 13 C NMR, EI-MS and elemental analysis. The in vitro screening of these molecules against urease explored that most of the compounds exhibit potent inhibitory potential against this enzyme. The compound9j, with IC50 value of 2.58 ± 0.02 µM, exhibited most promising inhibitory activity among the series, relative to standard thiourea having IC50 value of 21.11 ± 0.12 µM. In silico studies fully augmented the experimental enzyme inhibition results. Chemo-informatics analysis showed that synthesized compounds (9a–l ) mostly obeyed the Lipinski's rule. Molecular docking study suggested that ligand9j exhibited good binding energy value (−7.10 kcal/mol) and binds within the active region of target protein. So, on the basis of present investigation, it was inferred that9j may serve as a novel scaffold for designing more potent urease inhibitors.